The Application of COBIT Framework to Evaluate Information System Governance in National Business Technology Transformation Companies - Kraugusteeliana, Kraugusteeliana; Sri Wahyuningsih, Suluh; Hesti Indriana, Intan; Suryadi, Dikky; Munizu, Musran (SEULANGA SYSTEM PUBLISHER, 2024)
The purpose of this study is to determine how to assess information technology governance by utilizing the COBIT 5 framework and the domains of APO01 (Manage the IT Management Framework), EDM04 (Ensure Resource Optimization), and APO04 (Manage Innovation). The COBIT 5 architecture is employed in this study. Both qualitative and quantitative research methodologies were used in this study. Through surveys, interviews, and observations, we gathered primary data. The secondary data came from various existing sources, including websites, literature reviews, and the findings of other investigations. This study's information technology governance data analysis approach complies with COBIT 5's Assessment Process Activities. According to the analysis, the current state's capability value in the EDM04 domain is 1.8. In the meantime, the capability value is 2.9 for the anticipated circumstance. The APO01 domain's recent state results in a capability value of 1.7. In the meantime, the capability value is 3.1 for the expected circumstance. In the APO04 domain, the current state has a capability value 1.6. Under ideal circumstances, the business receives a capacity value of 3. This implies that the business needs to fulfill the prerequisites for level 2 process capacity indicators, which are now unfulfilled. For instance, producing papers outlining the management of the innovation process and documents evaluating rejected innovative ideas.